Pengaruh Kepemimpinan Transformasional, Budaya Organisasi, dan Motivasi terhadap Perilaku Berbagi Pengetahuan - Meildy Louisa Kese; Dylmoon Hidayat (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2021)
Knowledge sharing has important role in establishing and maintaining the quality of any organization especially in education area. Knowledge sharing is influenced by transformational leadership which builds a culture of sharing and motivates all members to practice it. This study aims to identify the effect of transformational leadership, organizational culture, and motivation to knowledge sharing behavior. This study utilizes a quantitative approach with a path analysis method to determine the effect of the coefficients of each variable. The data was collected by distributing questionnaires to 70 respondents at Sekolah XYZ Kupang. The result showed that (1) transformational leadership has no direct effect on knowledge sharing behavior; (2) organizational culture has a positive effect on knowledge sharing behavior; (3) motivation has a positive effect on knowledge sharing behavior; (4) transformational leadership has a positive effect on organizational culture; (5) transformational leadership has a positive effect on motivation; (6) transformational leadership has a positive effect on knowledge sharing behavior through organizational culture; (7) transformational leadership has a positive effect on knowledge sharing behavior through motivation.